2020
DOI: 10.1002/mp.13678
|View full text |Cite
|
Sign up to set email alerts
|

Machine and deep learning methods for radiomics

Abstract: Radiomics is an emerging area in quantitative image analysis that aims to relate large‐scale extracted imaging information to clinical and biological endpoints. The development of quantitative imaging methods along with machine learning has enabled the opportunity to move data science research towards translation for more personalized cancer treatments. Accumulating evidence has indeed demonstrated that noninvasive advanced imaging analytics, that is, radiomics, can reveal key components of tumor phenotype for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
254
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 344 publications
(257 citation statements)
references
References 139 publications
(266 reference statements)
2
254
0
1
Order By: Relevance
“…Machine learning (ML) is the discipline that builds mathematical models and computer algorithms to perform specific tasks by learning patterns and inferences directly from data using computers, without being explicitly programmed to conduct these tasks [10]. ML algorithms can be either used for supervised learning, where the machine is provided with output labels to be associated with a set of input variables, or unsupervised learning.…”
Section: Artificial Intelligence In Healthcarementioning
confidence: 99%
See 1 more Smart Citation
“…Machine learning (ML) is the discipline that builds mathematical models and computer algorithms to perform specific tasks by learning patterns and inferences directly from data using computers, without being explicitly programmed to conduct these tasks [10]. ML algorithms can be either used for supervised learning, where the machine is provided with output labels to be associated with a set of input variables, or unsupervised learning.…”
Section: Artificial Intelligence In Healthcarementioning
confidence: 99%
“…To reduce overfitting in DL, data augmentation (e.g., by the affine transformation of the images) during training is commonly implemented [10], and layers in the networks are specialized in reducing overfitting, such as dropout layers [108]. On the other side, DL suffers from other sources of uncertainties (e.g., the presence of many local minima in the loss function and the stochastic nature of training algorithms), so that repeating model training multiple times does not necessarily produce the same model [2].…”
Section: Data Size and Qualitymentioning
confidence: 99%
“…Repeatability is commonly assessed by the extraction of radiomics features from repeated acquisitions of images under identical or near-identical acquisition and processing parameters. In contrast, reproducibility of radiomics features, also called robustness, is measured if the acquisition parameters and applied measuring systems differ [36]. A recent review performed an extensive literature search and identified radiomics features that were shown to be repeatable and reproducible among the investigated studies [37].…”
Section: Limitationsmentioning
confidence: 99%
“…Another limitation to the application of radiomics models in clinical routine is the problem of interpretability of the extracted features and the generated models. Mostly, radiomics analysis are perceived as a "black box", i.e., it is very difficult to (clinically) interpret the generated predictions [36]. However, some methods to improve the interpretability of radiomics analyses have been developed, such as graph-based approaches for feature-based radiomics [44] or visualization tools for deep learning-based radiomics that highlight regions of the segmented tumor according to their importance for the prediction of the generated classifier [45].…”
Section: Limitationsmentioning
confidence: 99%
“…There are many publications and special issues dedicated to the usage of radiomics to support clinical applications in combination with recent spread of advanced machine learning methods. 3,4 Yet questions remain if the development of radiomics makes it ready for prospective clinical use. Herein, we brought in two medical physics experts both of whom have extensive knowledge in clinical practice and radiomics research.…”
mentioning
confidence: 99%